Testing local cocoa selections in three provinces in Sulawesi: (i) Productivity and resistance to cocoa pod borer and Phytophthora pod rot (black pod). (April 2015) - McMahon, Peter; Purung, Hussin bin; Lambert, Smilja; Mulia, Sahardi; Nurlaila,; Susilo, Agung W.; Sulistyowati, Endang; Sukamto, Sri; Israel, Muhajir; Saftar, Ashar; Amir, Arman; Purwantara, Agus; et al.
Abstract: Trials were established on smallholder cocoa farms in three provinces in Sulawesi to assess productivity and constitutive responses of local cocoa clones to cocoa pod borer (CPB) and Phytophthora pod rot (Ppr) in different environmental situations. Twelve clones per trial (local farmer-assisted selections or clones produced by hybridisation programs in East Java and Malaysia) were tested in the districts of Pinrang, Polewali-Mandar and North Kolaka, including four standards common to the trials: the Malaysian clone, PBC123, and three selections from Sulawesi farms. The clones were evaluated from the time they started fruiting in 2010 (about two years after planting) for two years during which time chemical pesticides were not applied. Otherwise farms were managed according to recommended practices, including harvesting each fortnight, fertiliser application and heavy and light pruning, depending on the season. Butter fat content was generally lower than 50% but was higher in three local selections in Pinrang, M04, RB and Panimbu Red. While strongly dependent on genotype, fat and shell content and pod values in the common standards showed some variation between sites. The bean size and fat content of PBC123 was low, but this clone yielded better than most of the clones tested. For the common standards, yield estimates obtained from average yield per tree were higher in Pinrang (735–1100 tons/ha/annum) than in N. Kolaka (342–894 ton/ha/annum) or Polewali-Mandar (485–899 tons/ha/annum) indicating a marked site-effect. The number of flowers produced was higher in the common standards in Pinrang. Soil parameters including pH and exchangeable calcium, magnesium and potassium were higher in Pinrang than in Polman, although both sites were deficient in soil nitrogen and organic carbon. Lower average CPB infestation rates in ripe pods for the two-year evaluation period occurred in Pinrang (48–66%) and Polewali-Mandar (19–68%) than in N. Kolaka (77–80%). In most of the clones, total and severe CPB incidence decreased during the high pod season but some selections, such as M04 and TR01, maintained a low total and severe CPB incidence in both the low and high pod seasons, indicating partial resistance. In the ripe pods of common standards, the highest average Ppr incidence (ranging from 10 to 14%) occurred in N. Kolaka, which had a higher annual rainfall than the other sites. In ripe pods in the Pinrang trial, Geni J, M06 and Panimbu Red had a low Ppr incidence (4.4–4.8%) while M04 was Ppr-susceptible (23%). Incidence of Helopeltis spp. was high in the immature pods of some clones (exceeding 30% of the total harvest in M01 and Geni J in Pinrang). The results show that the performance of clones is affected by the locality in which they are grown, as well as their genotype, indicating the importance of testing clones under different environmental conditions. While the trials confirmed the efficacy of farmer-assisted selection, they also indicated that clones resistant to CPB, were susceptible to Ppr or other pests/diseases, and vice versa. For example, local selection, M04, was highly susceptible to Ppr, yet resistant to CPB. Therefore, the results indicate the importance of efforts to screen the progeny of hybrid crosses that combine resistance and yield traits. Highlights: Promising local cocoa genotypes were selected with farmers for promising characteristics. Clones were tested in three locations in Sulawesi. Resistance occurred to either Phytophthora pod rot (Ppr) or cocoa pod borer, not both. Amount of rainfall influenced Ppr incidence and yield was higher at one of the sites. Bean fat content was generally below 50% but higher in some local selections.